Germany divided by circles - Robert de Vaugondy, Gilles, 1688-1766 (cartographer):::Creator:::::::::::: (France; Paris?)
Engraved color map of Germany from the mid 18th century, with latitude and longitude markings and the regions divided into circles, identified in French, which include: Westphalia, Haut Rhin, Elec. du Rhin, Souabe, Basse Saxe, Haute Saxe, Franconie, Baviere, Tirol, Pomeranie, Boheme, Autriche, Moravie.